Saints and psychiatry - Rumbaut, Ruben D. (Journal of religion and health, 1976)
SummaryThe Irish Saint Dympna, a distant and misty figure, with her martyrdom inspired a millenary tradition of family and community care for the mentally ill at Geel, in Belgium. She is the Catholic patron of the mentally afflicted.The French Saint Vincent de Paul, a powerful leader, took care of the insane and the poor in gentle ways; worked for reforms in hospitals, education, delinquency, and penology; founded religious orders dedicated to the sick; and set in motion the hospitals of La Salpêtrière and Le Bicêtre.The portuguese-Spaniard Saint John of God, a humble shepherd, a marginal soldier, an ignorant construction worker, and a modest salesman of books, has had more relevance to psychiatry than has Dympna, the martyr, or Vincent de Paul, the social reformer. No other saint has had more practical and sustained influence on hospital psychiatry than he, and it is a mystery of sorts that his name still awaits the distinguished place of honor it so richly deserves.